Understanding continued BNPL usage behavior in e-commerce: extended UTAUT2 with usage intention mediation - Indrajati Wahyuningtyastuti; Maya Ariyanti (International Journal of Accounting and Management Information Systems, 2025)
Purpose: This study aims to utilize an enhanced UTAUT2 model to examine the determinants influencing Indonesian customers' intentions and behaviors regarding the continued use of BNPL e-commerce services. Research/methodology: A quantitative cross-sectional survey was conducted with 450 users of BNPL services Indonesian e-commerce platforms, and the data were analyzed using structural equation modeling to assess direct and indirect relationships. Results: Performance expectancy, effort expectancy, trust, and habit significantly influenced continued usage, whereas perceived benefits and risks showed no significant impact among experienced digital users. Conclusions: Performance Expectancy, Effort Expectancy, and Trust are important drivers of the continued use of Buy Now Pay Later (BNPL) e-commerce services among Indonesian users, according to this study, which also shows that habit is the most important predictor of actual usage behavior. Limitations: The geographic breadth is limited to Indonesia, with possible selection bias toward current users, the sample focus on younger demographics impacts generalizability, and the cross-sectional methodology restricts causal inference. Contribution: This study contributes to fintech adoption theory by demonstrating the theoretical redundancy of traditional risk-benefit constructs in mature digital user contexts and emphasizing habit formation over initial adoption factors.